The Language Style Used by Elon Musk in English Speech: Future, A.I., And Mars - Affini, Nor; Hartiningsih, Sri (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2024)
Language style has an important role because interaction cannot go ahead if one does not speak the right style according to the situation. Furthermore, sometimes, there are still errors in language that are not adapted to situations when communicating in everyday life. This research aims to discover the types and functions of the language styles used in Elon Musk’s speech. The method used is descriptive qualitative. The object of this research is Elon Musk’s speech in the form of a transcript of a video from the YouTube channel entitled English Speech | Elon Musk: Future, A.I. and Mars (English Subtitles), which was released in 2018. The result shows that three types of language styles have been found: casual, consultative, and formal. Six functions have been found in this speech: referential, directive, expressive, phatic or social, poetic, and metalinguistic functions. Learning language style is very important as people can communicate with others according to where and with whom they speak so that the listener quickly understands the conversation.